HUBUNGAN PENGETAHUAN TENTANG KANKER SERVIKS DENGAN KEIKUTSERTAAN IVA TEST PADA KADER PKK DI DESA RAMBAH HILIR - Elvira Junita; Evi Cristina (Maternity and Neonatal : Jurnal Kebidanan, 2021)
Cervical cancer is the second leading cause of death for women in the world after breast cancer. the death rate from cervical cancer reached 18,279. This means, there are about 50 Indonesian women who died from cervical cancer. This figure jumped sharply compared to Globocon data in 2012 which stated that 26 Indonesian women died of cervical cancer each year (WHO, 2018). The purpose of this study was to determine the relationship between knowledge of cervical cancer and the participation of PKK cadres for the Visual Inspection of Acetic Acid in Rambah Hillir Village. Analytical survey research design with a cross sectional time approach. The population in this study were all active PKK cadres in Rambah Hilir Village, namely 32 people. The sampling technique in this study used a saturated sampling technique, namely that the entire population was sampled totaling 32 people. The results showed that 16 respondents (88%) who participated in the Visual Inspection of Acetic Acid had good knowledge. While respondents with sufficient knowledge who participated in the Visual Inspection of Acetic Acid were 8 people (80%) and respondents with insufficient knowledge participated in the Acetic Acid Visual Inspection Examination as many as 1 person (5%). Analysis of research results with the Chi-Square test obtained the value of Pvalue 0.0001. The conclusion in this study is that there is a significant relationship between knowledge of cervical cancer and the participation of PKK cadres in conducting a visual inspection of acetic acid.